The Causal Role of Phoneme Awareness and Letter-Sound Knowledge in Learning to Read - Hulme, Charles; Bowyer-Crane, Claudine; Carroll, Julia M.; Duff, Fiona J.; Snowling, Margaret J. (Psychological Science, 2012)
There is good evidence that phoneme awareness and letter-sound knowledge are reliable longitudinal predictors of learning to read, though whether they have a causal effect remains uncertain. In this article, we present the results of a mediation analysis using data from a previous large-scale intervention study. We found that a phonology and reading intervention that taught letter-sound knowledge and phoneme awareness produced significant improvements in these two skills and in later word-level reading and spelling skills. Improvements in letter-sound knowledge and phoneme awareness at the end of the intervention fully mediated the improvements seen in children's word-level literacy skills 5 months after the intervention finished. Our findings support the conclusion that letter-sound knowledge and phoneme awareness are two causal influences on the development of children's early literacy skills.